PERAN GURU DALAM MENANAMKAN KEPEDULIAN SISWA PADA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM - Irawan, Lestari; Munirah, Munirah; Datunsolang, Rinaldi (Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Padangsidimpuan, 2024)
AbstractIslamic History and Culture Education is one of the subjects taught at Madrasah Ibtidaiyah Muhammadiyah Gorontalo North City Branch. However, many students do not understand the importance of Islamic history and culture, and tend to find this lesson boring. Therefore, it is important to develop effective and interesting learning methods for students to increase their interest and understanding of Islamic history and culture. The type of research used is qualitative. Qualitative research is research used to examine the natural conditions of objects (as opposed to experiments). Instilling students' awareness of the subject of Islamic cultural history requires an active and strategic role from the teacher. At MI Muhammadiyah North City, teachers have several important roles which are implemented through various approaches and methods to achieve this goal. Apart from that, they must also be able to integrate cultural and religious values in teaching, so that students can understand the relevance of history in everyday life.